The Application of the Discovery Learning Model Assisted by Picture Card Media in Improving Indonesian Language Learning Outcomes - Riska Puput Apriliani; Rinja Efendi (Universitas Pahlawan Tuanku Tambusai, 2026)
Indonesian language learning in elementary schools requires a learning model that can improve student activity and learning outcomes. However, the Indonesian language learning outcomes of grade III C students of SD Negeri 010 Ujung Batu are still low with a learning completion percentage of only 48%. This study aims to determine the application of the discovery learning model assisted by picture cards in improving students' Indonesian language learning outcomes. This study is a Classroom Action Research (CAR) conducted in two cycles, each consisting of two meetings, with 21 students. Data collection techniques used learning outcome tests and observation sheets for student and teacher activities. The results showed that learning completion increased to 90% at the end of cycle II with an average score of 84.76. Student activity also increased from 55% in cycle I to 90% in cycle II. Thus, the application of the discovery learning model assisted by picture cards can improve students' Indonesian language learning outcomes.